Multi-pollutant synergistic purification multifunctional composite material and preparation method thereof

By adopting multifunctional composite materials, using aliphatic polyamines, piperazine and its derivatives, manganese and vanadium species and combining ultrasonic loading and hot air microwave drying technology, the coordinated capture of SO2, CO2 and NOx in industrial waste gases is solved. The collection and purification problem has achieved efficient multi-pollutant capture and recycling of resources.

CN119455647APending Publication Date: 2025-02-18ZHEJIANG HAILIANG ENVIRONMENTAL MATERIALS +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411848543.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively coordinate the capture and purify SO2, CO2 and NOx in industrial waste gas, and the technological development of the regeneration link is insufficient.

Method used

Using a multifunctional composite material whose raw material composition includes aliphatic polyamine or polyamine species, piperazine and its derivatives, manganese and vanadium species, and natural clay carriers, coupled with hot air microwaves by ultrasonic or oscillator loading method. Prepared by drying technology, forming efficient multi-pollutant collaborative capture and regeneration composite materials.

Benefits of technology

Efficient adsorption and purification of multi-pollutants are achieved, the capture efficiency of CO2, SO2 and NOx is improved, and the captured CO2 is converted into useful chemicals or fuels through regeneration technology, reducing the dependence on fossil resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455647A_ABST
    Figure CN119455647A_ABST
Patent Text Reader

Abstract

The invention discloses a multifunctional composite material for synergistically purifying multiple pollutants and a preparation method of the multifunctional composite material, belongs to the field of waste gas purification, and is used for realizing industrial desulfurization, decarburization and denitrification, and the multifunctional composite material is prepared from the following raw material components: 20-40% of aliphatic polyamine or polyamine species; 20-30% of piperazine and derivative species thereof; 10-20% of manganese and vanadium species; and the balance of a natural clay carrier. The preparation method comprises the following steps: firstly, preparing an aqueous solution of TEPA and manganous nitrate, loading the aqueous solution of TEPA and manganous nitrate on a porous carrier, then drying to obtain a solid amino decarburization and denitrification composite material, finally loading synthesized HPP on the solid amino decarburization and denitrification composite material by dropwise adding or spraying, and then drying to obtain the amino multi-pollutant synergistic trapping and regenerating composite material. The step-by-step preparation mode can ensure the quality and stability of each link.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of waste gas purification, and in particular relates to a pollutant collaborative purification composite material and a preparation method thereof. Background Art

[0002] In today's context of environmental protection and sustainable development, SO 2 , CO 2 The collaborative capture and regeneration technology of NOx is gaining increasing attention.

[0003] With the acceleration of industrialization and the continuous growth of energy consumption, the carbon dioxide (CO 2 ), sulfur dioxide (SO 2 ) and nitrogen oxides (NOx) continue to rise, posing serious challenges to the global climate and ecological environment. 2 As the main greenhouse gas, its excessive emission leads to global warming, causing a series of problems such as rising sea levels and an increase in extreme climate events. 2 The emission of NOx will form acid rain, causing serious damage to soil, water bodies, buildings, etc. The emission of NOx will cause acid deposition, ozone layer depletion, water eutrophication, photochemical pollution, etc., which will not only affect air quality, but also have a profound impact on human health, ecosystems and global climate change. In order to meet these challenges, scientists are committed to developing efficient multi-pollutant synergistic capture technology. This technology aims to simultaneously capture SO in industrial waste gas. 2 , CO 2 and NOx, reducing their negative impact on the environment and achieving the goal of emission reduction.

[0004] The regeneration process after collaborative capture is also crucial. Regeneration technology can convert the captured SO 2 , CO 2 and NOx to convert them into useful substances or store them safely. For example, thermal treatment can be used to remove carbon dioxide and sulfur dioxide respectively; chemical methods can be used to remove CO 2 Conversion into fuels, chemicals or used in enhanced oil recovery and other fields; for SO 2 It can be recycled and used to produce industrial products such as sulfuric acid. The development of multi-pollutant synergistic capture and regeneration technology not only helps reduce the emission of greenhouse gases and harmful gases, but also provides a new way to achieve the recycling of resources. Today, as the world works together to cope with climate change and environmental pollution, this technology has broad development prospects and important practical significance.

[0005] The solid amine composite material is prepared by loading organic amine onto a porous material by ultrasonic or oscillator loading method, grafting or in-situ polymerization. The selection of carrier and organic amine type has an effect on the CO 2 The adsorption performance is significantly affected. Studies have shown that mesoporous and macroporous structures are conducive to the entry of organic amine molecules into the porous material carrier without completely blocking its pores; larger pore volume and specific surface area are conducive to the uniform dispersion of more organic amines and amine molecules; the special functional group structure on the surface of the carrier, such as silanol, is conducive to the connection of amino groups with the surface of the carrier by chemical bonds, thereby improving the stability of organic amines in the carrier. Piperazine compounds have important applications in the field of desulfurization, and their preparation methods are diverse. One common method is to synthesize piperazine by reacting ethylene dichloride and ammonia, and then obtain piperazine compounds for desulfurization by derivatization. Another method is to prepare it through a specific cyclization reaction using diamines as raw materials. Biosynthetic pathways can also be used to produce piperazine precursors with the help of specific microorganisms, and then chemical conversion is carried out. Reaction conditions such as temperature, pressure, catalyst, etc. need to be controlled during the preparation process to improve yield and purity. Manganese has a variety of variable valence states and can effectively react with nitrogen oxides in a wide temperature range to achieve a high denitrification efficiency. Manganese-based materials have a certain ability to treat nitrogen oxides at different concentrations and under different working conditions, and can be flexibly applied to a variety of industrial flue gas denitrification scenarios. Compared with some traditional denitrification agents, manganese-based materials generally do not produce secondary pollution during the reaction process, and the by-products are relatively easy to handle. Manganese-based denitrification is mainly based on redox reactions. Under appropriate temperature, oxygen and other conditions, manganese oxides (such as MnO 2 etc.) and nitrogen oxides (NO, NO 2 MnO 2 For example, it can oxidize NO to NO 2 , itself is restored, and then NO 2 It can further react with other substances (such as reducing agents or under certain conditions) to convert into harmless substances such as nitrogen, thereby achieving the purpose of removing nitrogen oxides from flue gas. This process is continuously circulated, allowing the manganese-based denitrification material to continuously and effectively carry out the denitrification reaction.

[0006] This technology can capture three types of polluting gases at the same time, greatly reducing the emission of atmospheric pollutants and greenhouse gases. In industrial production, such as thermal power generation, it can effectively reduce the harmful substances produced by the combustion of fossil fuels and accelerate the process of reaching the carbon peak. In addition, the captured CO 2It can be converted into useful chemicals or fuels, reduce dependence on fossil resources, and help achieve carbon neutrality. Secondly, in terms of industrial development, it promotes the green upgrading of the energy industry. It encourages energy companies to improve production processes, improve energy efficiency, reduce pollutant emissions, and achieve a clean and low-carbon transformation of the energy structure. At the same time, the research and development and application of technology drive the development of upstream and downstream industries, including composite material production and environmental protection equipment manufacturing, create green employment opportunities, and promote the green upgrading of the industrial structure. Furthermore, from an international perspective, the active development of this technology demonstrates China's strength and attitude in the field of environmental protection and enhances its international influence. China can share technical experience and achievements with other countries and contribute to global carbon emission reduction. It can also promote international cooperation, carry out joint research and development and project cooperation, introduce foreign advanced technology and experience, and promote Chinese technology and products to the international market. Finally, from the perspective of environmental quality, synergistic capture can effectively reduce the emission of polluting gases and the greenhouse effect, reduce the frequency of acid rain, alleviate the greenhouse effect, and improve the quality of the atmospheric environment. Good environmental quality lays the foundation for ecosystem stability and biodiversity protection, reduces damage to soil, water and vegetation, and protects ecological balance. Therefore, the development of a new type of high-efficiency and multifunctional composite material is not only the key to achieving industrial desulfurization, decarbonization and denitrification, but also one of the important measures to promote the realization of the dual carbon goals. Summary of the invention

[0007] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a multifunctional composite material for the coordinated purification of multiple pollutants and a preparation method thereof, so as to achieve industrial desulfurization, decarbonization and denitrification, and have good desulfurization, decarbonization and denitrification effects.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] First, a multifunctional composite material suitable for coordinated purification of multiple pollutants is provided. The raw material components for preparing the multifunctional composite material include, by mass:

[0010] Aliphatic polyamine or polyamine species 20-40%

[0011] Piperazine and its derivatives 20-30%

[0012] Manganese and vanadium species 10-20%

[0013] and the balance is a natural clay carrier.

[0014] Preferably, the aliphatic polyamine or polyamine species is tetraethylenepentamine;

[0015] And / or, the piperazine and its derivative species are N,N'-di(2-hydroxypropyl)piperazine;

[0016] and / or, the manganese and vanadium species are manganese dioxide or vanadium pentoxide species;

[0017] And / or, the natural clay carrier is one or at least two of native vermiculite, kaolin, microcline, bentonite and barium feldspar.

[0018] In addition, the present invention also provides a method for preparing a multifunctional composite material suitable for coordinated purification of multiple pollutants, which is prepared using raw materials of the multifunctional composite material and comprises the following steps:

[0019] Dissolving aliphatic polyamine or polyamine species, manganese and vanadium species together to form a mixed solution A;

[0020] The natural clay is processed to obtain a porous carrier;

[0021] The mixed solution A is loaded with a carrier to form solid particles loaded on the carrier;

[0022] The solid particles are dried to obtain solid amino NO x &CO 2 capture composite materials;

[0023] Synthesize piperazine and its derivative species into piperazine solution;

[0024] The piperazine solution is loaded onto the solid amine NOx & CO by dripping or spraying. 2 Capture composite materials; load the solid amine NOx & CO 2 The capture composite material is dried to obtain a composite material for the synergistic capture and regeneration of multiple amino pollutants.

[0025] Preferably, native vermiculite is selected as a natural clay carrier, and the native vermiculite is heat-treated at 800° C. for 10 minutes to rapidly increase its interlayer volume to obtain expanded vermiculite; the expanded vermiculite is acid-activated and selectively etched to obtain acid-activated expanded vermiculite-derived silica.

[0026] Preferably, the acid reagent used for acid activation is one or more of citric acid, acetic acid, sulfonic acid, and ethylenediaminetetraacetic acid. When citric acid is used, the solid-liquid mass ratio of citric acid is 1:(3-10), and the citric acid concentration is 0.5 mol / L.

[0027] Preferably, the carrier is dispersed in the mixed solution A, and the CO 2 、SO 2 The adsorption component and the low-temperature denitrification active component are loaded on a carrier and then dried using a hot air microwave coupling drying technology.

[0028] Preferably, the hot air microwave coupled drying technology is implemented under the following conditions: temperature of 100-200°C and air velocity of 1-5m / s under standard atmospheric pressure; or drying under microwave vacuum conditions, temperature of 40°C-150°C, microwave power of 20-200W, and vacuum degree of 200-500Pa.

[0029] Preferably, the solid particles are initially dried by hot air microwave coupling drying technology and then transferred to a vacuum drying oven for calcination again to obtain solid amino NO x &CO 2 The composite material is captured and placed in a vacuum drying oven at a heating rate of 5-10°C / min, a calcination temperature of 400-600°C, and a constant temperature calcination time of 2-6 hours.

[0030] Preferably, the preparation method of the piperazine solution comprises the following steps: mixing a certain amount of anhydrous piperazine with a certain amount of methanol under magnetic stirring at 65-75°C, adding an appropriate amount of propylene oxide, and reacting at this temperature for 2 hours, wherein the mass ratio of anhydrous piperazine to methanol is 1:(1-3), and the mass ratio of anhydrous piperazine to propylene oxide is 1:(1-2).

[0031] Preferably, the content of active components in the prepared composite material for synergistic capture and regeneration of multiple pollutants by amino groups is 0.1-50wt.%, and the content of each component is calculated in the form of its oxide; and / or, the loaded solid amino NOx & CO 2 The capture composite material is calcined in a vacuum drying oven, with a heating rate of 5-10°C / min, a calcination temperature of 400-600°C, and a constant temperature calcination time of 2-6 hours.

[0032] The present invention adopts the above technical solution and has the following beneficial effects:

[0033] (1) The composite material of the present invention has a high multi-pollutant adsorption efficiency. The following are the principle advantages of the preparation method of the composite material. High dispersion improves adsorption performance: TEPA and manganese nitrate are highly dispersed in the carrier, so that the active ingredients can be more fully in contact with the target gas. This dispersion state helps to increase the specific surface area of ​​the composite material, thereby improving the adsorption of CO 2 At the same time, the evenly dispersed active components can more effectively exert their chemical adsorption effect and enhance the adsorption effect of the composite material.

[0034] (2) Multi-component synergistic enhancement of capture capacity: Adding an appropriate amount of N,N'-di(2-hydroxypropyl)piperazine (HPP) and TEPA to form a composite material, different amine components can work synergistically to target SO 2 and CO 2The combination of multiple amine groups may provide more adsorption sites and different adsorption mechanisms, thereby improving the comprehensive capture efficiency of the two gases.

[0035] (3) Step-by-step preparation to ensure stability: The preparation process is divided into multiple steps. First, an aqueous solution of TEPA and manganese nitrate is prepared and loaded on a porous carrier. Then, it is dried to obtain a solid amine-based denitrification and desulfurization composite material. Finally, the synthesized HPP is loaded on it by dripping or spraying. This step-by-step preparation method can ensure the quality and stability of each link. For example, the spray loading process allows TEPA to fully enter the carrier, the hot air microwave coupling drying process can remove excess moisture while allowing it to be fully loaded, and the final loading of HPP further enhances the composite material's resistance to SO 2 and CO 2 The synergistic capture and regeneration capabilities.

[0036] (4) The preparation method of the present invention is simple. It only requires mixing the materials and then using hot air microwave coupling drying technology to obtain a highly uniformly dispersed, small-particle decarbonization and denitrification composite material. Then, the desulfurization, decarbonization and denitrification of industrial tail gas can be achieved through a spraying device.

[0037] The specific technical solutions of the present invention and the beneficial effects thereof will be disclosed in detail in the following specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The desulfurization / denitrification / decarbonization efficiency diagram of six composite materials. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is explained and described below in conjunction with the embodiments of the present invention, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work are all within the protection scope of the present invention.

[0040] Those skilled in the art will appreciate that, in the absence of conflict, the features in the following embodiments and implementations may be combined with each other.

[0041] The embodiments of the present invention provide a novel composite material suitable for the coordinated purification of multiple pollutants in industrial flue gas, and a preparation method and application thereof.

[0042] A multifunctional composite material suitable for coordinated purification of multiple pollutants, wherein the raw material components for preparing the multifunctional composite material include, by mass:

[0043] Aliphatic polyamine or polyamine species 20-40%

[0044] Piperazine and its derivatives 20-30%

[0045] Manganese and vanadium species 10-20%

[0046] and the balance is a natural clay carrier.

[0047] For example, 30% aliphatic polyamine or polymeric amine species, 25% piperazine and its derivative species, 15% manganese and vanadium species, and the balance natural clay carrier.

[0048] For example, 20% aliphatic polyamine or polymeric amine species, 30% piperazine and its derivative species, 20% manganese and vanadium species, and the balance natural clay carrier.

[0049] For example, 40% aliphatic polyamine or polymeric amine species, 20% piperazine and its derivative species, 10% manganese and vanadium species, and the balance natural clay carrier.

[0050] The composite material is a doped composite porous material synthesized by ultrasonic impregnation and hot air microwave coupling drying technology. The modified material uses modified natural clay as a carrier and tetraethylenepentamine (TEPA), polyethyleneimine (PEI) and other amine species as CO 2 The adsorption components are piperazine species such as N,N'-bis(2-hydroxypropyl)piperazine (HPP) as SO 2 Adsorption components, with manganese and vanadium species as low-temperature denitrification active components.

[0051] The natural clay carrier includes one or more of native vermiculite, kaolin, microcline, bentonite, and barium feldspar, and its components are (Mg, Fe, Al) x (Si,Al) y ·ZH 2 O.S. 2 O 8 2- / TiO 2 , K + / Na + / Ca 2+ Al 2 Si 2 O 8 - , BaAl 2 / Si 2 O 8 2- .

[0052] The composite material has a large specific surface area (300-600m 2 / g), uniform particle size (2-4μm), large number of surface alkaline sites (greater than 50μmol / g), small average pore size (less than 10nm), CO2 Its strong adsorption capacity (greater than 3.45mmol / g) and other characteristics meet the needs of collaborative purification and are particularly suitable for solving the difficult problem of flue gas pollution reduction and carbon reduction.

[0053] The present invention also provides a method for preparing the collaborative purification material, which has the advantages of simple operation and simple equipment requirements, and comprises the following steps:

[0054] Dissolving aliphatic polyamine or polyamine species, manganese and vanadium species together to form a mixed solution A;

[0055] The natural clay is processed to obtain a porous carrier;

[0056] The mixed solution A is loaded with a carrier to form solid particles loaded on the carrier;

[0057] The solid particles are dried to obtain solid amine NOx & CO 2 capture composite materials;

[0058] Synthesize piperazine and its derivative species into piperazine solution;

[0059] The piperazine solution is loaded onto the solid amine NOx & CO by dripping or spraying. 2 Capture composite materials, load solid amine NOx & CO 2 The capture composite material is dried to obtain a composite material for the synergistic capture and regeneration of multiple amino pollutants.

[0060] Native vermiculite can be selected as a natural clay carrier, and the native vermiculite is heat-treated at 800°C for 10 minutes to rapidly increase its interlayer volume, thereby obtaining expanded vermiculite; and the expanded vermiculite is acid-activated and selectively etched to obtain acid-activated expanded vermiculite-derived silica.

[0061] The acid reagent used for acid activation is one or more of citric acid, acetic acid, sulfonic acid, and ethylenediaminetetraacetic acid. When citric acid is used, the solid-liquid mass ratio of citric acid is 1:(3-10), such as 1:6, and the citric acid concentration is 0.5 mol / L.

[0062] The carrier is dispersed in the mixed solution A, and the CO 2 、SO 2 The adsorption component and the low-temperature denitration active component are loaded on the carrier, and then dried by hot air microwave coupling drying technology. The hot air microwave coupling drying technology is implemented under the following conditions: temperature: 100-200°C, air flow rate: 1-5m / s under standard atmospheric pressure; or drying under microwave vacuum conditions, temperature: 40°C-150°C, microwave power: 20-200W, vacuum degree: 200-500Pa.

[0063] The solid particles were initially dried by hot air microwave coupling drying technology and then transferred to a vacuum drying oven for calcination again to obtain solid amine NOx & CO 2 The composite material is captured and placed in a vacuum drying oven at a heating rate of 5-10°C / min, a calcination temperature of 400-600°C, and a constant temperature calcination time of 2-6 hours.

[0064] The preparation method of the piperazine solution is:

[0065] Under magnetic stirring at 65-75°C, a certain amount of anhydrous piperazine is mixed with a certain amount of methanol, and then an appropriate amount of propylene oxide is added, and the reaction is kept warm for 2 hours, wherein the mass ratio of anhydrous piperazine to methanol is 1:(1-3), for example, 1:1, 1:2, 1:3, and the mass ratio of anhydrous piperazine to propylene oxide is 1:(1-2), for example, 1:1, 1:1.5, 1:2.

[0066] Alternatively, a certain amount of anhydrous piperazine is mixed with a certain amount of methanol, and the mass ratio of anhydrous piperazine to methanol is 1:(1-3), such as 1:1.5, 1:2.

[0067] The loaded solid amine NOx & CO 2 The capture composite material is calcined in a vacuum drying oven, with a heating rate of 5-10°C / min, a calcination temperature of 400-600°C, and a constant temperature calcination time of 2-6 hours.

[0068] In addition, the content of active components in the prepared composite material for synergistic capture and regeneration of multiple pollutants based on amino groups is 0.1-50wt.%, and the content of each component is calculated in the form of its oxide.

[0069] Example 1

[0070] The preparation method of the multifunctional composite material proposed by the present invention comprises the following steps:

[0071] (S1) Add 50 ml TEPA to 100 ml ethanol C 2 H 5 OH solution, stirring for 30 min until the mixture is uniform, to obtain a mixed solution A;

[0072] (S2) 50g manganese nitrate Mn(NO 3 ) 2 Add to the mixed solution A, stir for 30 min until mixed evenly, to obtain a mixed solution B;

[0073] (S3) 100 g of native vermiculite (VMT) was heat-treated and expanded to increase its interlayer volume rapidly, thereby obtaining expanded vermiculite (EV), and then the EV was activated by 500 ml of 0.5 mol / L citric acid and selectively etched to obtain acid-activated expanded vermiculite-derived silica, thereby synthesizing a vermiculite-derived silica carrier (AEV) with a hierarchical porous structure;

[0074] (S4) The above-mentioned mixed solution is loaded with the above-mentioned synthesized vermiculite-derived silica carrier (AEV) with hierarchical porous structure. The porous carrier is dispersed in the mixed solution B, and the CO 2 、SO 2 The adsorption component and the low-temperature denitrification active component are loaded on a vermiculite-derived silica carrier (AEV), and then quickly dried using a hot air microwave coupling drying technology, the implementation conditions being: temperature: 100-200°C under standard atmospheric pressure, air flow rate of 1-5m / s or drying under microwave vacuum conditions, temperature of 40°C-150°C, microwave power of 20-200W, vacuum degree of 200-500Pa. The solvent in the droplets is rapidly evaporated to form a solid particle loaded on the AEV carrier.

[0075] (S5) transferring the loaded composite material to a vacuum drying oven and drying for 12 hours to remove the remaining water to obtain a solid amine-based decarbonization and denitrification composite material;

[0076] (S6) 34.3 g of anhydrous piperazine C was added under magnetic stirring at 65-75 °C. 4 H 10 N 2 With 34.3g methanol CH 3 OH is fully mixed and 46.7g of propylene oxide C is added dropwise 2 H 4 O, keep warm for 2h to obtain HPP alcohol solution;

[0077] (S7) Finally, the HPP alcohol solution is loaded onto the solid amine-based composite material prepared in S5 by a dripping or spraying device, the program heating rate is 5-10°C / min, the calcination temperature is 400-600°C, and the constant temperature calcination time is 2-6 hours, and finally a multifunctional desulfurization, decarbonization and denitrification composite material is obtained.

[0078] Comparative Example 2

[0079] The difference between this comparative example and Example 1 is that the ethanol in S1 is replaced with an equal volume of deionized water, and the other conditions are the same as those in Example 1.

[0080] Comparative Example 3

[0081] The difference between this comparative example and Example 1 is that the native vermiculite (VMT) in S3 is changed to the metal organic framework carrier AlFu.

[0082] Step 1, dissolve 0.15 g of PEI (polyetherimide) in 124 ml of deionized water, and stir magnetically for 30 minutes to obtain a mixed solution 1.

[0083] Step 2, 49.6 mmol C 4 H 2 Na 2 O 4 Dissolve in the above mixed solution 1 and stir magnetically for 30 minutes.

[0084] Step 3, remove the solvent water by rotary evaporation at 70°C, and then put the solid powder into a muffle furnace and calcine at 410°C for 4 hours to obtain a white solid as a metal organic framework carrier.

[0085] Comparative Example 4

[0086] The difference between this comparative example and Example 1 is that the oscillator or ultrasonic immersion in S4 is changed to magnetic stirring immersion, and the other conditions are the same as those in Example 1.

[0087] Comparative Example 5

[0088] The difference between this comparative example and Example 1 is that the HPP alcohol solution in S6 is changed to monoethanolamine (MEA) or diethanolamine (DEA), and the other conditions are the same as those in Example 1.

[0089] Comparative Example 6

[0090] The difference between this comparative example and Example 1 is that the HPP alcohol solution in S6 is replaced with N-hydroxypropylpiperazine (HEP), and the other conditions are the same as those in Example 1.

[0091] Step 1, dissolving piperazine in water to form a piperazine solution;

[0092] Step 2, slowly drop propylene oxide into the piperazine solution under stirring at a temperature of 50°C-100°C. Propylene oxide and piperazine undergo a ring-opening addition reaction, the epoxy bond of propylene oxide opens and combines with the nitrogen atom in the piperazine molecule to generate N-hydroxypropylpiperazine. The remaining conditions are the same as those in Example 1.

[0093] Application Examples

[0094] The multifunctional composite materials prepared in Example 1 and Comparative Examples 2-6 were tested for their decarbonization, desulfurization and denitrification performance, and simulated flue gas synergistic removal experiments were conducted. The experimental conditions were as follows: Figure 1 As shown:

[0095] The desulfurization test method is: control the gas concentration (vol%) through the mass flow meter, SO 2 :500ppm, N 2 To balance the gas, the industrial tail gas is continuously introduced into the sulfur absorbent for reaction. The reaction temperature is 150°C, the reaction pressure is 0.3 MPa, and the mass space velocity of the industrial tail gas is 0.3 h -1 , detect the sulfur dioxide flow at the outlet after 180 minutes; the desulfurization efficiency calculation formula is η=(C1-C2) / C1×100%, where C1 is SO 2 The inlet concentration of C2 is SO 2 The outlet concentration is obtained by testing with a flue gas analyzer.

[0096] The decarburization test method is: control the gas concentration (vol%) by mass flow meter, CO: 500ppm, N 2 The industrial tail gas for balancing gas was continuously introduced into the adsorbent for reaction. The reaction temperature was 150°C, the reaction pressure was 0.3 MPa, the inlet flow rate was 30 mL / min, and the CO was detected by gas chromatograph at the outlet. 2 The flow rate of carbon dioxide adsorption is calculated by F is the mixed gas inlet flow rate, mL / min; t is CO 2 Adsorption time, min; C 0 , C represent the reactor inlet and outlet CO respectively 2 Concentration, mol / L; qt is CO at adsorption time t 2 Adsorption amount, mmol / g, when the reactor outlet CO 2 The concentration is equal to the inlet CO 2 Concentration, i.e. C / C 0 =1.0, the adsorbent reaches the equilibrium adsorption state, and the adsorption amount at this time is called the saturated adsorption amount.

[0097] The test method for denitrification is: control the concentration (vol%) of each gas through a mass flow meter, NO x :500ppm, N 2 To balance the gas, the industrial tail gas is continuously introduced into the sulfur absorbent for reaction. The reaction temperature is 150°C, the reaction pressure is 0.3 MPa, and the mass space velocity of the industrial tail gas is 0.3 h -1 , after 240 minutes, the nitrogen oxide flow rate at the outlet is detected; the denitrification efficiency calculation formula is η=(C3-C4) / C3×100%, where C3 is NO x The inlet concentration of C4 is NO x The outlet concentration is obtained by testing with a flue gas analyzer.

[0098] Table 1: Desulfurization, decarbonization and denitrification performance test results of multifunctional composite materials

[0099]

[0100] Depend on Figure 1 It can be seen from the test results that the new high-efficiency multifunctional desulfurization, decarbonization and denitrification composite materials of Example 1 and Comparative Example 3 of the present invention have excellent desulfurization and decarbonization efficiency, and also have a denitrification efficiency of more than 80% at 150°C. In the desulfurization process, the principle of desulfurization of piperazine solid composite materials is mainly based on chemical adsorption and acid-base neutralization reaction. Piperazine contains nitrogen atoms in its molecular structure, and there are lone pairs of electrons on the nitrogen atoms. These lone pairs of electrons can interact with sulfur dioxide molecules to form chemical bonds, thereby adsorbing sulfur dioxide molecules to the surface of piperazine solid composite materials. This chemical adsorption effect is relatively strong, and sulfur dioxide can be more firmly bound to the composite material. In addition, piperazine solid composite materials have a certain pore structure and a large specific surface area, which provides a large number of adsorption sites for the adsorption of sulfur dioxide. Sulfur dioxide molecules can enter the pores of the composite material, undergo chemical adsorption reactions with the active sites on the surface of the composite material, and then be adsorbed. Piperazine is an organic base and has a certain alkalinity. Sulfur dioxide is an acidic gas, and when sulfur dioxide contacts piperazine solid composite materials, an acid-base neutralization reaction occurs. During the reaction, the alkaline groups in the piperazine molecule react with the acidic parts in the sulfur dioxide molecule to generate corresponding salt compounds. The salt compounds have a certain stability on the surface or inside of the composite material and are not easy to decompose or desorb. This enables the piperazine solid composite material to effectively maintain its adsorption capacity for sulfur dioxide until the composite material reaches a saturated state or is regenerated under specific conditions.

[0101] During the decarbonization process, the amine group is alkaline and carbon dioxide (CO 2 ) is an acidic gas, and an acid-base neutralization reaction will occur between the two. The nitrogen atom on the amine group will provide a lone pair of electrons to react with CO 2 The carbon atoms in the molecule form coordination bonds, 2 Fixed on the composite material. The amine groups in the amine-based solid composite material are fixed on the composite material. 2 Hydrogen bonds may also form between molecules. Although the strength of hydrogen bonds is relatively weaker than that of chemical bonds, they can also enhance the 2 In the pore structure of the composite material, the synergistic effect of multiple hydrogen bonds can make CO 2 The molecules are adsorbed more stably. The amine-based solid composite material has a porous structure with a large specific surface area and abundant pores. 2 Van der Waals forces are generated between molecules and the surface of the composite material. This intermolecular force makes CO 2The molecules can attach to the inner surface of the pores of the composite material. However, physical adsorption is weaker than chemical adsorption, and the adsorption and desorption processes are relatively easy to occur. The pore structure and pore size of the composite material have an impact on CO 2 The appropriate pore size can provide enough space for CO 2 The molecules enter and form a certain steric hindrance in the pores, making CO 2 The molecules do not easily escape from the composite material, thus improving the adsorption effect.

[0102] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.

Claims

1. A multifunctional composite material suitable for coordinated purification of multiple pollutants, characterized in that: The raw material components for preparing the multifunctional composite material include, by mass: Aliphatic polyamine or polyamine species 20-40% Piperazine and its derivatives 20-30% Manganese and vanadium species 10-20% and the balance is a natural clay carrier.

2. The multifunctional composite material according to claim 1, characterized in that: The aliphatic polyamine or polyamine species is tetraethylenepentamine; And / or, the piperazine and its derivative species are N,N'-di(2-hydroxypropyl)piperazine; and / or, the manganese and vanadium species are manganese dioxide or vanadium pentoxide species; And / or, the natural clay carrier is one or at least two of native vermiculite, kaolin, microcline, bentonite and barium feldspar.

3. A method for preparing a multifunctional composite material suitable for coordinated purification of multiple pollutants, using the raw materials of the multifunctional composite material according to claim 1 or 2 for preparation, characterized in that: The method comprises the following steps: dissolving aliphatic polyamine or polyamine species, manganese and vanadium species together to form a mixed solution A; The natural clay is processed to obtain a porous carrier; The mixed solution A is loaded with a carrier to form solid particles loaded on the carrier; The solid particles are dried to obtain solid amino NO x &CO2 capture composite materials; Synthesize piperazine and its derivative species into piperazine solution; The piperazine solution is loaded onto a solid amine-based NOx & CO2 capture composite material by dripping or spraying; the loaded solid amine-based NOx & CO2 capture composite material is dried to obtain an amine-based composite material for synergistic capture and regeneration of multiple pollutants.

4. The method for preparing the multifunctional composite material according to claim 3, characterized in that: Native vermiculite was selected as a natural clay carrier, and the native vermiculite was heat-treated at 800°C for 10 minutes to rapidly increase its interlayer volume, thereby obtaining expanded vermiculite. The expanded vermiculite was then acid-activated and selectively etched to obtain acid-activated expanded vermiculite-derived silica.

5. The method for preparing the multifunctional composite material according to claim 4, characterized in that: The acid reagent used for acid activation is one or more of citric acid, acetic acid, sulfonic acid, and ethylenediaminetetraacetic acid. When citric acid is used, the solid-liquid mass ratio of citric acid is 1: (3-10), and the citric acid concentration is 0.5 mol / L.

6. The method for preparing the multifunctional composite material according to claim 3, characterized in that: The carrier is dispersed in the mixed solution A, and the CO2, SO2 adsorption components and the low-temperature denitrification active components are loaded on the carrier by ultrasonic wave or oscillator, and then dried by hot air microwave coupling drying technology.

7. The method for preparing the multifunctional composite material according to claim 6, characterized in that: The implementation conditions of the hot air microwave coupling drying technology are: temperature under standard atmospheric pressure: 100-200°C, air flow rate of 1-5m / s; or drying under microwave vacuum conditions, temperature of 40°C-150°C, microwave power of 20-200W, vacuum degree of 200-500Pa.

8. The method for preparing the multifunctional composite material according to claim 6, characterized in that: The solid particles were initially dried by hot air microwave coupling drying technology and then transferred to a vacuum drying oven for calcination again to obtain solid amino NO x &CO2 capture composite material, in a vacuum drying oven, the heating rate is 5-10℃ / min, the calcination temperature is 400-600℃, and the constant temperature calcination time is 2-6 hours.

9. The method for preparing the multifunctional composite material according to claim 3, characterized in that: The preparation method of the piperazine solution comprises the following steps: mixing a certain amount of anhydrous piperazine with a certain amount of methanol under magnetic stirring at 65-75° C., adding an appropriate amount of propylene oxide, and reacting for 2 hours at this temperature, wherein the mass ratio of anhydrous piperazine to methanol is 1:(1-3), and the mass ratio of anhydrous piperazine to propylene oxide is 1:(1-2).

10. The method for preparing the multifunctional composite material according to claim 3, characterized in that: The content of active components in the prepared composite material for synergistic capture and regeneration of multiple pollutants by amino groups is 0.1-50wt.%, and the content of each component is calculated in the form of its oxide; and / or, the loaded solid amino-based NOx & CO2 capture composite material is calcined in a vacuum drying oven, with a heating rate of 5-10°C / min, a calcination temperature of 400-600°C, and a constant temperature calcination time of 2-6 hours.